Preliminary study of effective copper indium sulfide (CuInS2) quantum dots as photo-sensitizer in solar cell - Nurul Syafiqah Mohamed Mustakim,; Javad Safaei,; Ubani, Charles Ahamefula; Suhaila Sepeai,; Norasikin Ahmad Ludin,; Mohd Asri Mat Teridie,; Mohd Adib Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Recent studies showed that quantum dots (QDs) materials such as cadmium (Cd) and lead (Pb) are commonly used as sensitizer in solar cell applications. This is mainly because they have high potential in light harvesting. However, these materials are highly toxicity and very harmful to the environment. Therefore, current investigation reports the performance of quantum dots sensitized solar cells (QDSSCs) based on non-toxicity CuInS2 QDs by using solvothermal process. TiO2 paste were deposited by doctor blade method on transparent conducting fluorine doped tin oxide (FTO) glass substrates. The CuInS2 nano sized QDs were controlled by different solvothermal reaction times of 2 hours, 4 hours, 6 hours and 8 hours. In this study, the morphology, structural and optical properties of prepared TiO2/CuInS2 QDs thin films were investigated by using Transmission Electron Microscope (TEM), Atomic Force Microscope (AFM), X-ray Diffraction (XRD) and Ultra-Violet-Visible Near Infrared Spectrophotometer (UV-Vis). The diameter of CuInS2 QDs was found to be increased from 3.19 nm to 8.67 nm with longer reaction time. Results showed that CuInS2 QDs with longer reaction time produced higher conversion efficiency. Based on the experiment done, CuInS2 QDs with 8 hours reaction time produced the best power conversion efficiency; 0.035 %. Regarding the considerable efficiencies obtained, pointed out that CuInS2 QDs can be introduced as an effective photosensitizer for making efficient QDSSCs devices.